Axon guidance molecules and pain - Damo, Elisa; Simonetti, Manuela (Cells, 2022)
Chronic pain is a debilitating condition that influences the social, economic, and psychological aspects of patients’ lives. Hence, the need for better treatment is drawing extensive interest from the research community. Developmental molecules such as Wnt, ephrins, and semaphorins are acknowledged as central players in the proper growth of a biological system. Their receptors and ligands are expressed in a wide variety in both neurons and glial cells, which are implicated in pain development, maintenance, and resolution. Thereby, it is not surprising that the impairment of those pathways affects the activities and functions of the entire cell. Evidence indicates aberrant activation of their pathways in the nervous system in rodent models of chronic pain. In those conditions, Wnt, ephrin, and semaphorin signaling participate in enhancing neuronal excitability, peripheral sensitization, synaptic plasticity, and the production and release of inflammatory cytokines. This review summarizes the current knowledge on three main developmental pathways and their mechanisms linked with the pathogenesis and progression of pain, considering their impacts on neuronal and glial cells in experimental animal models. Elucidations of the downstream pathways may provide a new mechanism for the involvement of Wnt, ephrin, and semaphorin pathways in pain chronicity.
Gesehen am 21.12.2022